2015
DOI: 10.5897/ajb2015.14770
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the genetic diversity of 48 groundnut (Arachis hypogaea L.) genotypes in the Guinea savanna agro-ecology of Ghana, using microsatellite-based markers

Abstract: Groundnut (Arachis hypogaea L.) is the most important grain legume in Ghana. However, its production is constrained by a myriad of biotic and abiotic stresses which necessitate the development and use of superior varieties for increased yield. Germplasm characterisation both at the phenotypic and molecular level is important in all plant breeding programs. The aim of this study was to characterise selected advanced breeding groundnut lines with different phenotypic attributes at the molecular level using simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Tsigbey et al [1] reported that in a typical farming community in Northern Ghana, about 90% of farm families engaged in groundnut cultivation. Oteng-Frimpong et al [2] also found that about 70% of groundnuts produced in Ghana are concentrated in the northern regions of Ghana. Te cultivation is carried out on both commercial and subsistence bases.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Tsigbey et al [1] reported that in a typical farming community in Northern Ghana, about 90% of farm families engaged in groundnut cultivation. Oteng-Frimpong et al [2] also found that about 70% of groundnuts produced in Ghana are concentrated in the northern regions of Ghana. Te cultivation is carried out on both commercial and subsistence bases.…”
Section: Introductionmentioning
confidence: 96%
“…Tese genera include Staphylococcus (S. aureus, S. saprophyticus, and S. epidermidis), Proteus (P. vulgaris, P. myxofaciens, P. hauseri, P. mirabilis, and P. penneri), Escherichia (E. coli O157), Bacillus (Bacillus cereus, B. subtilis, B licheniformis, B. larvae, B. lentimorbus, B. popilliae, and B. sphaericus), and Micrococcus (M. roseus and M. luteus). Table 3 shows the bacterial contaminant 1Values are means of triplicate determinations from three independent trials; ± � standard deviation; TCC � total coliform count; TVC � total viable counts; BS � Bolgatanga sample; NS � Navrongo sample; GS � Bongo sample; CS � Chiana sample 2. Means with the same letter as superscript in a column are signifcantly diferent (P < 0.05).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Africa holds the maximum global area under groundnut cultivation (i.e., 11.7 m ha representing 47.56% of total area cultivated). Meanwhile, its yield are very low (929 kg ha −1 ) compared with that of the Americas (3,632 kg ha −1 ) (Ajeigbe et al, 2015) due to a myriad of biotic and abiotic stresses (Oteng-Frimpong et al, 2015). This has resulted in a series of interventions aimed at improving pod yields on farmers' fields.…”
Section: Introductionmentioning
confidence: 99%